2012
DOI: 10.1007/s00101-012-1994-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimikrobielle Therapie bei Patienten nach Verbrennungstrauma

Abstract: Infections are a great diagnostic and therapeutic challenge in intensive care patients with burn injuries. The major problems are due to bacteria with hospital-acquired multiresistance to antibiotics but fungal and viral infections may also be life-threatening. The main key points addressing pharmacotherapy with antibiotic, antifungal and antiviral agents in this special setting are exact diagnosis, early therapy with suitable drugs, adequate duration of treatment and adequate doses based on pharmacokinetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…We did not find that pneumonia was correlated with excessive fluid volume administered early in the hospital course, but we did find that the presence of inhalational injury increased the risk of pneumonia by more than 2-fold within the first week of injury. Several other studies have found an association between pneumonia and the presence of inhalational injuries [22][23][24][25]. We did not find a statistical correlation between TBSA and pneumonia, however, as has been seen in some of these studies [23].…”
Section: Discussioncontrasting
confidence: 62%
“…We did not find that pneumonia was correlated with excessive fluid volume administered early in the hospital course, but we did find that the presence of inhalational injury increased the risk of pneumonia by more than 2-fold within the first week of injury. Several other studies have found an association between pneumonia and the presence of inhalational injuries [22][23][24][25]. We did not find a statistical correlation between TBSA and pneumonia, however, as has been seen in some of these studies [23].…”
Section: Discussioncontrasting
confidence: 62%
“…PA's ability to form a biofilm enables a persistent wound infection and a significant delay in wound healing [9]. Burn wound infections can prolong the hospital stay of patients by up to 9 days or even cause major complications [34,35]. Thus, the main objective in burn wound management is prevention and effective therapy of infected burn wound sites, so that the incidence of major complications such as sepsis and death can be reduced and healing of the damaged skin can be achieved [36].…”
Section: Discussionmentioning
confidence: 99%
“…[5659] For prophylaxis purpose, azole or candin agents are always used but not polyenes. Polyenes either amphotericin B or its liposome are the traditional classical antifungal agents, their broad-spectrum antifungal effects are confirmed by many doctors.…”
Section: Prophylaxis Of Bifimentioning
confidence: 99%